Gastrointestinal tract-based implicit measures for cognition, emotion and behavior - van Erp, Jan B. F. (Frontiers in Computer Science, 2022)
Implicit physiological measures such as heart rate and skin conductance convey information about someone’s cognitive or affective state. Currently, gastrointestinal (GI) tract-based markers are not yet considered while both the organs involved as well as the microbiota populating the GI tract are bidirectionally connected to the brain and have a relation to emotion, cognition and behavior. This makes GI tract-based measures relevant and interesting, especially because the relation may be causal, and because they have a different timescale than current physiological measures. This perspective paper 1) presents the (mechanistic) involvement of the GI tract and its microbiota in emotion, cognition and behavior; 2) explores the added value of microbiome-based implicit measures as complementary to existing measures; and 3) sets the priorities to move forward. Five potential measures are proposed and discussed in more detail: bowel movement, short-chain fatty acids, tyrosine and tryptophan, GI tract flora composition, and cytokine levels. We conclude 1) that the involvement of the GI tract in emotion, cognition and behavior is undisputed, 2) that GI tract-based implicit measures are still in a conceptual phase of development but show potential and 3) that the first step to bring this field forward is to start validation studies in healthy humans and that are designed in the context of implicit measurements.